Characterization of the effects on ovalbumin mRNA of aminomethyl-trimethylpsoralen photoreaction with hen oviduct mRNA. - Liarakos, C D (1987)
We have described the reaction of 4'-aminomethyl-4,5',8-trimethylpsoralen (AMT) with hen oviduct mRNA and have investigated the specific effects of AMT photoaddition on ovalbumin mRNA which constitutes 60-70% of oviduct mRNA. The photoreaction of AMT with hen oviduct mRNA appeared to occur in two phases - a rapid monoaddition followed by a slower conversion of monoadducts to diadducts (i.e. crosslinking). Both nondenaturing and denaturing gel electrophoresis revealed a photoreaction time dependent increase in ovalbumin mRNA electrophoretic mobility indicating the formation of a progressively more compact molecular structure. Identical analysis of photoreacted rabbit globin mRNA revealed no change in electrophoretic mobility suggesting that AMT was stabilizing the AU rich secondary structure of ovalbumin mRNA but having no similar effect on the relatively GC rich secondary structure of globin mRNA. Ovalbumin-specific DNA primer extension was used to demonstrate the selective and secondary structure specific photoaddition of AMT to uracil bases at the 5' end of ovalbumin mRNA.